Implementasi Analytical Hierarchy Proses Pada Sistem Pendukung Keputusan Pemilihan Beras Berkualitas - Rismayani, Rismayani; SY, Hasyrif; Herlinda, Herlinda; MZ, St. Naziha Nasif; Tulwahdah, Farida (Computer Engineering Departement, Universitas Komputer Indonesia, 2024)
This study aims to process a Decision support system in selecting quality rice that fits the criteria and decision alternatives that apply the Analytical Hierarchy Process (AHP) and also builds a web-based system to process the data. The Logistics Affairs Agency (BULOG) is a state-owned company engaged in food logistics. These agencies include logistics/warehousing, surveys and eradication of pests, supply of plastic sacks, transportation business, trade in food commodities and retail industry. The method used is the Analytical Hierarchy Process (AHP) which produces a hierarchical order or ranking of alternatives, this system is expected to assist in the selection of quality rice. The result of the research is to build a web-based system by implementing AHP in determining quality rice and based on accuracy testing, 100% results are obtained. Based on the functional testing of the system using a black box valid results were brought, then in logic testing using a white box found data that was free from errors.